Sources of information: a necessary approach - Olga Ferragut Rodríguez; Belisa Machín Torres; Olina Very Montelongo Sánchez (Revista MENDIVE, 2009)
In the last years it has taken place in Cuba an increase in the documentary production, in the information activity and the organization of the systems and services of information. To know about the sources of information in which we need to look up according to the type of information we are going to use is everybody's task.